A new genus of the Tympanophorus lineage of the subtribe Anisolinina from Madagascar (Coleoptera: Staphylinidae: Staphylininae: Staphylinini) - Janák, Jiří (Zootaxa, 2018)
A new genus of the Tympanophorus lineage of the subtribe Anisolinina, Janalia gen. nov. with the type species Janalia jarmilae sp. nov., from East Madagascar is described and illustrated. A modified key to the genera of the subtribe Anisolinina is presented.